Unravelling the Myth of Effective Teaching in Mathematics - John O'Donoghue; Mark Prendergast (Irish Journal of Academic Practice, 2014)
Effective teaching is the backbone of any successful education system with many arguing that it is the single biggest contributor to student success. However despite such importance, significant differences in teacher effectiveness are still evident in Irish classrooms at all levels of education. This research investigates the influence that individual teachers can have on students’ enjoyment of mathematics at second level and attempts to unravel the myth of effective teaching. The research started out as a followon study that further analysed data collected by the authors when they designed a pedagogical framework with the aim of promoting student interest in algebra through effective teaching of the domain. This paper focuses entirely upon the quantitative results of the evaluation of that study with regard to whether there are differences in the enjoyment scores of students’ in different classes as a result of their individual teachers. The paper also looks to unravel the myth of effective teaching through a series of focus group interviews and a detailed literature review.